Royal charity theatre production - The Star, (2012)
INFRASTRUCTURE University Kuala Lumpur (IUKL) together with charity organisation Nadi Malaysia and Universiti Putra Malaysia (UPM) will stage a royal charity musical theatre production in December. A launching ceremony for this collaboration was recently held at IUKL's multi-purpose hall